The effects of alcohol on spontaneous clearance of acute hepatitis C virus infection in females versus males. (1st December 2016) - Tsui, Judith I.; Mirzazadeh, Ali; Hahn, Judith A.; Maher, Lisa; Bruneau, Julie; Grebely, Jason; Hellard, Margaret; Kim, Arthur Y.; Shoukry, Naglaa H.; Cox, Andrea L.; Prins, Maria; Dore, Gregory J.; et al.
Highlights: The study included data from prospective cohorts of substance users with acute HCV. Rates of spontaneous clearance of HCV were higher among those who did not drink alcohol. A stronger, significant effect of alcohol use was found for women compared to men. Abstract: Background: Approximately one quarter of persons exposed to hepatitis C virus (HCV) will spontaneously clear infection. We undertook this study to investigate the impact of alcohol on likelihood of HCV spontaneous viral clearance stratified by sex groups. Methods: Pooled data from an international collaboration of prospective observational studies of incident HIV and HCV infection in high-risk cohorts (the InC3 Study) was restricted to 411 persons (or 560.7 person-years of observation) with documented acute HCV infection and data regarding alcohol use. The predictor of interest was self-reported alcohol use at or after estimated date of incident HCV infection and the outcome was HCV spontaneous clearance. Sex stratified Cox proportional hazards models were used to evaluate the association between alcohol and spontaneous clearance, adjusting for age, race/ethnicity, and IFNL4 genotype. Results: The median age was 28.5 years, 30.4% were women, 87.2% were white, and 71.8% reported alcohol use at or after incident infection. There were 89 (21.6%) cases of spontaneous clearance observed, 39 (31.2%) among women and 50 (17.5%) in men (p < 0.01). Overall, spontaneous clearance occurred less frequently among participants who drank alcohol compared to those who did not drink (18.9% v. 28.5%, p = 0.03). After adjustment for other covariates, alcohol was significantly and independently associated with lower relative hazards for spontaneous clearance of HCV in women (AHR = 0.35; 95% CI: 0.19–0.66; p = 0.001) but not in men (AHR = 0.63; 95% CI: 0.36–1.09; p = 0.10). Conclusion: Results indicate that abstaining from drinking alcohol may increase the likelihood of spontaneous clearance among women.